Exploring Children's Science and Mathematics Ability with Leaf Diary: A Case Study - Yulia, Resti; Mahyuddin, Nenny; Nurhafizah, Nurhafizah; Sulong, Komareeyah (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2021)
Purpose – This study aims to explore Leaf diary activity to develop the Science and Mathematics ability of children aged 6 years.Design/methods/approach – The method used is a case study. The unit of analysis is based on predetermined criteria, using the purposive sampling technique. Research informants are mentors and children involved in leaf diary activity in Solok, Indonesia. The data collection process used participant observation, documentation, and in-depth interviews. Data analysis used structural analysis techniques.Findings – The results showed that leaf diary activity could develop: (1) children's ability to classify leaves based on their shape; (2) the ability to compare leaf size based on length, as well as large or small size.Research implications/limitations – All research informants were from Solok District, Indonesia, which may limit the generalizability of the findings.Practical implications – This case study contributes to the implementation of Leaf diary as an alternative activity that teachers or parents can do to develop children's science and mathematics ability.Originality/value – Leaf diary activity can help children explore the natural environment so that basic science and math abilities and concepts in this activity are carried out well. Paper type Case study